PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING (DL) UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN PERAWATAN WAJAH TIDAK BERMASALAH SECARA MANUAL DI SMKN 1 BUDURAN SIDOARJO - Tasya Agita; Wilujeng, Biyan Yesi; Faidah, Mutimmatul; Megasari, Dindy Sinta (Jurnal Tata Rias, 2025)
Abstract This research focuses on exploring the application and enhancement of the discovery learning approach to improve students' academic results in manual facial care at SMKN 1 Buduran. The motivation for this research comes from students' unsatisfactory final learning achievements, which stem from their limited engagement in the educational process. The methodology employed in this study is Classroom Action Research (CAR), conducted in two stages: planning, execution, monitoring, and evaluation. A total of 34 students from the Grade X Skin Beauty Program participated in this study. Data collection methods included observation sheets, assessments of learning outcomes, and documentation review. Implementing the discovery learning approach has led to increased student participation and comprehension, as shown by the rise in the average learning outcome scores from pre-cycle to cycle II. The outcomes related to facial care topics that were not closely tracked have been positively affected by the discovery learning technique. Keywords: Discovey Learning, learning outcomes, facial care, beauty learning